Pemberdayaan Masyarakat Tani Oleh Pemerintah Desa Gunung Kecamatan Simo Kabupaten Boyolali Dalam Peningkatan Taraf Kesejahteraan Petani Berdasarkan Regulasi Peraturan Gubernur Jawa Tengah No 55 Tahun 2019 Tentang Perencanaan Perlindungan dan Pemberdayaan Masyarakat Tani Provinsi Jawa Tengah - Saputra, Yogi Anggara Fiqi; Riswanda, Riswanda; Yusuf, Maulana (Universitas Labuhanbatu, 2024)
Gunung Village in Simo District is an area that has a low harvested area compared to other villages. It is recorded from the official page in the Simo District statistics source from the Simo District agricultural extension agency, that Gunung Village has a harvested area of 221 (Ha) in 2020 even though the population is working as farmers is much greater than in other villages. This research aims to determine the Empowerment of Farming Communities by the Government of Gunung Village, Simo District, Boyolali Regency in Increasing the Level of Farmers' Welfare Based on Central Java Governor Regulation No. 55 of 2019 concerning Planning for the Protection and Empowerment of Farming Communities in Central Java Province. The method used in this research is a case study with a descriptive qualitative research approach. Data collection techniques include observation, interviews and documentation. The results of this research indicate that the Gunung Village Government, Simo District, Boyolali Regency has not fully implemented Central Java Governor Regulation No. 55 of 2019 concerning Planning for the Protection and Empowerment of Farming Communities in Central Java Province. However, the regional government must also increase its role in implementing the Governor's Regulation so that the standard of living of farmers in Central Java, especially in Mountain Village, can improve further.